Effects of bolted connections' properties on natural dynamic characteristics of corner-supported modular steel buildings. (November 2022) - Farajian, M.; Sharafi, P.; Alembagheri, M.; Kildashti, K.; Bigdeli, A.
Abstract: Corner-supported modular steel building, made of volumetric units, is an efficient construction system for the next generation of industrialised building construction. The mechanical performance of joints, including inter-modular connections and beam-to-column connections, or so-called intra-modular connections, and their effects on the dynamic behaviour of these structures have remained a research hotspot in the design of modular buildings. This paper studies the effect of bolted vertical inter-module and intra-modular connections' characteristics on the dynamic properties of a corner-supported modular steel frame using an experimental program and numerical simulations. To that end, a half-scaled vertically stacked 3-storey modular building, instrumented with highly sensitive accelerometers, is used to scrutinise the effect of different configurations of inter- and intra-modular connections on the dynamic characteristics of the structure. The acceleration responses of the system under randomly generated artificial vibrations and pure ambient vibrations are synchronously recorded. Then, dynamic characteristics of the modular building are extracted by employing the Operational Modal Analysis (OMA). Finally, finite element models are developed, and a comprehensive parametric study is conducted to verify the experimental results and evaluate the influence of connections' behaviour on the frequencies of the structure. The results indicate that while the behaviour of inter-connection has no significant effect on the natural frequency of the building, variation of intra-connections' properties and their configurations can lead to a change in fundamental frequency of modular buildings. Shear stiffness of connections was found to be the most effective factor influencing the frequencies of modular structures.